Towards a Climate-Neutral Europe Curbing the Trend - Delbeke, Jos; Vis, Peter (2020)
This book explains the EU's climate policies in an accessible way, to demonstrate the step-by-step approach that has been used to develop these policies, and the ways in which they have been tested and further improved in the light of experience. The latest changes to the legislation are fully explained throughout. The chapters throughout this volume show that no single policy instrument can bring down greenhouse gas emissions. The challenge facing the EU, as for many countries that have made pledges under the Paris Agreement, is to put together a toolbox of policy instruments that is coherent, delivers emissions reductions, and is cost-effective. The book stands out by the fact it covers the EU's emissions trading system, the energy sector and other economic sectors, including their development in the context of international climate policy. This accessible book will be of great relevance to students, scholars and policy makers alike.